p38δ controls Mitogen- and Stress-activated Kinase-1 (MSK1) function in response to toll-like receptor activation in macrophages - Díaz-Mora, Ester; González-Romero, Diego; Meireles-da-Silva, Marta; Sanz-Ezquerro, Juan José; Cuenda, Ana (Frontiers in Cell and Developmental Biology, 2023)
Mitogen- and Stress-activated Kinase (MSK) 1 is a nuclear protein, activated by p38α Mitogen-Activated Kinase (MAPK) and extracellular signal-regulated kinase (ERK1/2), that modulate the production of certain cytokines in macrophages. Using knockout cells and specific kinase inhibitors, we show that, besides to p38α and ERK1/2, another p38MAPK, p38δ mediates MSK phosphorylation and activation, in LPS-stimulated macrophages. Additionally, recombinant MSK1 was phosphorylated and activated by recombinant p38δ, to the same extent than by p38α, in in vitro experiments. Moreover, the phosphorylation of the transcription factors CREB and ATF1, that are MSK physiological substrates, and the expression of the CREB-dependent gene encoding DUSP1, were impaired in p38δ-deficient macrophages. Also, the transcription of IL-1Ra mRNA, that is MSK-dependent, was reduced. Our results indicate that MSK activation can be one possible mechanism by which p38δ regulates the production of a variety of inflammatory molecules involved in immune innate response.